Strategi Pembelajaran Bahasa Inggris bagi Pembelajar Muda Menggunakan Media Digital sebagai Bagian dari Implementasi Kurikulum Merdeka - Winia Waziana; Widi Andewi; Ricco Herdiyan Saputra; Tri Yuni Hendrowati (Journal of Education and Teaching Learning, 2025)
To keep up with the times, English learning needs to be learned from elementary school. There are still many human resources in Indonesia who are not proficient or even unable to speak English. This is due to the uneven distribution of English teaching in schools. Many schools did not teach English Education due to several factors, including: first, English is not a compulsory subject in schools. Second, the lack of teachers who can teach English. Third, the lack of learning media that support English teaching. Fourth, the location of the school is far from the city. Fifth, the lack of awareness of the school about the importance of English learning. The purpose of creating this digital learning application and its application in English subjects is to make English learning more enjoyable, thereby increasing students' interest in learning. With this application program, it is hoped that students can easily learn and understand as much vocabulary as possible and how to pronounce the vocabulary in English. The type of research method is a qualitative method. The results show the increasing enthusiasm of SDN 10 Way Lima students for English lessons through mobile web-based digital learning applications, because this application can provide a more interesting learning experience for students. This application can facilitate the process of learning English. It can be accessed anytime and anywhere. Flexible learning time makes it easier for teachers to make student learning activities at school more active, so that learning objectives will be implemented effectively.